2022
DOI: 10.1039/d2ra04643a
|View full text |Cite
|
Sign up to set email alerts
|

Corncob biochar combined with Bacillus subtilis to reduce Cd availability in low Cd-contaminated soil

Abstract: There were multiple mechanisms worked during 400 °C CB@B immobilized Cd in soil, and reduction of availability Cd reached 69%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
0
0
Order By: Relevance
“…Furthermore, in our study, soil amendments promoted the upregulation of some rare bacterial taxa (Bacillus, Candidatus_Solibacter, and Streptomyces) (relative abundance < 0.1%), which might be helpful for the immobilization of heavy metals. Earlier research has indicated that the presence of Bacillus in pot experiments enhanced the immobilization of Cd in soil [52,53]. Candidatus_Solibacter has been proven to be a core microorganism in soils with different toxic heavy metals [28,54].…”
Section: Effects Of Soil Amendments On Rhizosphere Bacterial Communit...mentioning
confidence: 99%
“…Furthermore, in our study, soil amendments promoted the upregulation of some rare bacterial taxa (Bacillus, Candidatus_Solibacter, and Streptomyces) (relative abundance < 0.1%), which might be helpful for the immobilization of heavy metals. Earlier research has indicated that the presence of Bacillus in pot experiments enhanced the immobilization of Cd in soil [52,53]. Candidatus_Solibacter has been proven to be a core microorganism in soils with different toxic heavy metals [28,54].…”
Section: Effects Of Soil Amendments On Rhizosphere Bacterial Communit...mentioning
confidence: 99%